2014
DOI: 10.1242/dev.099564
|View full text |Cite
|
Sign up to set email alerts
|

Ubpy controls the stability of the ESCRT-0 subunit Hrs in development

Abstract: Ubiquitylated developmental membrane signaling proteins are often internalized for endocytic trafficking, through which endosomal sorting complexes required for transport (ESCRT) act sequentially to deliver internalized cargos to lysosomes. The ESCRT function in endocytic sorting is well established; however, it is not fully understood how the sorting machinery itself is regulated. Here, we show that Ubiquitin isopeptidase Y (Ubpy) plays a conserved role in vivo in the homeostasis of an essential ESCRT-0 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 46 publications
(55 reference statements)
2
33
0
Order By: Relevance
“…While both K63-specific DUB AMSH and non-ub-chain specific USP8 balance the receptor degradation and recycling, exhibiting negative regulation of lysosomal sorting, the roles of AMSH and USP8 are worthy of digging at depth [29]. AMSH and USP8 showed a positive role in the downregulation of protease-activated receptor 2 and additionally, USP8 exhibits pleiotropic effects considering its regulatory role in ESCRT-0 and receptors per se [30, 31]. …”
Section: Main Roles Of Dubsmentioning
confidence: 99%
“…While both K63-specific DUB AMSH and non-ub-chain specific USP8 balance the receptor degradation and recycling, exhibiting negative regulation of lysosomal sorting, the roles of AMSH and USP8 are worthy of digging at depth [29]. AMSH and USP8 showed a positive role in the downregulation of protease-activated receptor 2 and additionally, USP8 exhibits pleiotropic effects considering its regulatory role in ESCRT-0 and receptors per se [30, 31]. …”
Section: Main Roles Of Dubsmentioning
confidence: 99%
“…In some experiments, MG132 (50 mM; Sigma) or ALLN (50 mM; Sigma) was added to cultured cells or wing discs for 6-8 hr to inhibit proteasome activity, while E64 (50 mM; Sigma), leupeptin (50 mM; Sigma), or NH 4 Cl (10 mM) was used to disrupt lysosome function. Cycloheximide (50 mg/ml; Sigma) was added to S2 cells for 6 hr to inhibit nascent protein synthesis (Zhang et al, 2014), while colchicine (30 mM; Sigma) was added to S2 cells for 12 hr to induce mitotic arrest (Rogers et al, 2009). …”
Section: Cell Culture and Drug Treatmentsmentioning
confidence: 99%
“…Earlier studies extensively showed the implication of UBPY in the endosomal pathway in both Drosophila and mammalian cultured cell models [1926, 41, 42]. We hypothesized that the autophagy flux blockade and impaired lysosomes formation induced by Ubpy loss-of-function might be related to its function in the endosomal pathway, suggesting that the overall endosomal process is crucial for lysosomal biogenesis.…”
Section: Discussionmentioning
confidence: 91%